Upsilococconeis dapalistriata gen. nov. & comb. nov. (Bacillariophyta) – a pantropical marine member of Cocconeidaceae - Riaux-Gobin Catherine; Witkowski Andrzej; Risjani Yenny; Yunianta Yunianta; Berteaux-Lecellier Véronique; Kryk Adrian; Peszek Łukasz; Daniszewska-Kowalczyk Genowefa (Oceanological and Hydrobiological Studies)
Cocconeis dapalistriata, first described as a member of the genus Cocconeis, is re-examined due to its unique ultrastructure. Both valvocopulae of this taxon show significant differences compared to those found in the genus Cocconeis. They are expanded and show some similarities with those found in Amphicocconeis. On the other hand, terminal parts of the raphe valve (RV) in C. dapalistriata are simple and the raphe valve (RV) striae are composed of small round areolae with a hymenate occlusion with radial slits, similar to those observed in Cocconeis. Campyloneis and Xenococconeis also have expanded valvocopulae but with numerous morphological differences compared to those found in C. dapalistriata. Furthermore, the areolae of the sternum valve (SV) in C. dapalistriata are occluded by a concave velum with no apparent internal slits, and externally ornamented with irregular silica crystals. Upsilococconeis Riaux-Gobin, Witkowski & Risjani gen. nov. is proposed to accommodate the latter taxon. First described from the Western Indian Ocean (Mascarenes), it was subsequently listed from the Western Pacific Ocean (Guam), the South Pacific Ocean (French Polynesia and New Caledonia) and from the Eastern Indian Ocean (Indonesia), and thus may qualify as pantropical.